1972
DOI: 10.1083/jcb.55.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Ultramicroincineration of Thin-Sectioned Tissue

Abstract: Low temperature ultramicroincineration was employed to determine the morphological localization of "structure-bound" mineral and/or metallic elements within biological cells at the electron microscope level . This technique chemically removes organic material from thin sections of tissues with reactive, excited oxygen instead of heat as used in a furnace . The remaining ash representing the mineral/metallic ultrastructure of cells is advantageous for ultrastructural studies because incineration without applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In contrast, Hohman & Schraer (1972) found that lack of Os04 fixation made no difference in the SEM appearance of most cellular structures in totally ashed sections of avian shell gland tissue. Similarly, Yoshino et al (1982) found no difference in the post plasma SEM appearances of nuclear membranes and zymogen granules for Os04-stained versus unstained pancreas cell sections.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, Hohman & Schraer (1972) found that lack of Os04 fixation made no difference in the SEM appearance of most cellular structures in totally ashed sections of avian shell gland tissue. Similarly, Yoshino et al (1982) found no difference in the post plasma SEM appearances of nuclear membranes and zymogen granules for Os04-stained versus unstained pancreas cell sections.…”
Section: Discussionmentioning
confidence: 76%
“…Applied to thin sections of plasticembedded, fixed material, this treatment has been shown to produce ash patterns with considerable ultrastructural detail (Thomas, 1964;Thomas & Greenawalt, 1968). However, X-ray microanalytical studies of such preparations have so far used conventional microprobes (Frazier, 1971 ;Hohman & Schraer, 1972;Thomas & Corlett, 1973) and questions relating to the sensitivity increase and the spatial resolution achievable by the total system were not considered. We have examined the 0022-2720/78/0800-0269 932.00 0 1978 The Royal Microscopical Society 269 ash patterns produced by plasma microincineration of thin, fixed, plastic sections using a high-resolution electron microscope interfaced to an X-ray spectrometer as an initial step towards applying plasma microincineration to thin, frozen-dried cryosections.…”
Section: Introductionmentioning
confidence: 99%
“…megaterium spores in bulk; however, no X-ray microanalyses of single spores before and after low-temperature ashing are available. Low-temperature ashing has also been used as a preconcentration step for elemental detection and localization (Thomas 1974;Hohman 1974;Barnard and Thomas 1978;Brenna and Morrison 1984).…”
Section: Microincineration Mechanisms Of Sporesmentioning
confidence: 99%
“…Ashing generally increases elemental X-ray intensities of biological specimens (Albright and Lewis 1965;Hohman and Schraer 1972;Scherrer and Gerhardt 1972;Meyer and Stewart 1977; Barnard and Thomas 1978;Adamec et al 1979).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation